A study on Volumetric and Viscometric Properties for the Mixtures of DMF and Other Alcohols from Temperatures ranges 303.15K to 323.15K - Khan, Md. Zaved Hossain; Uddin, Md Helal; Islam, Md Shahrul; Khan, G.M Arifuzzaman; Muhit, Md. Abdullah Al; Ferdaus, Jannatul; Momin, Md. Abdul; Rahman, SK Shahinur (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
Densities, p, and viscosities, ?, of four binary systems: N,N-dimethyl formamide (DMF) + 1-propanol, DMF + 2-propanol, DMF + butanol and DMF + 1-pentanol have been measured at five different temperatures ranging form 303.15K to 323.15K at an interval of 5K. Excess molar volumes were found to be negative over the entire concentration ranges. The negative excess molar volume decreases with the increase of chain length of alcohol, the magnitude follows the order DMF+ 1-propanol >, + 2-propanol >, +butanol >, + 1-pentanol. The change of viscosity has been found to be sensitive to the chain length of alcohols. Excess viscosities and Grunberg- Nissan interaction parameters have been found to be positive for DMF + 1-propanol and DMF + 2-propanol systems, and negative for other two systems DMF + butanol and DMF + 1-pentanol. The thermodynamic energy of activation; such as, positive ?G#E each also compatible with the observation.